Measuring the Success of E-learning at SMA Negeri 1 Kroya by Adopting the Delone and McLean Model - Septi Fajarwati; Excel Ervinta Desty; Desty Rakhmawati (Jurnal Pendidikan Edutama, 2026)
This study aims to measure the success of the e-learning system implemented at SMA Negeri 1 Kroya by adopting the DeLone and McLean Information Systems Success Model. A descriptive quantitative approach was employed, with data collected through observations, interviews, and questionnaires distributed to 300 students selected randomly from a population of 1,004 students. The data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS software. The evaluation focused on six constructs: system quality, information quality, service quality, system use, user satisfaction, and net benefits. The results indicate that the model has adequate explanatory power in explaining system use, user satisfaction, and net benefits. Hypothesis testing shows that information quality and service quality significantly affect system use, while system quality and information quality significantly influence user satisfaction. In addition, system use and user satisfaction have a significant impact on net benefits. However, system quality does not significantly affect system use, and service quality does not significantly influence user satisfaction. Indirect effect analysis reveals that user satisfaction plays a more dominant mediating role than system use. These findings highlight that user satisfaction and quality of experience are key factors in determining the success of e-learning implementation.